Forty-Five Years of Caterpillar Rearing in Area de Conservación Guanacaste (ACG) Northwestern Costa Rica: DNA Barcodes, BINs, and a First Description of Plant–Caterpillar–Ichneumonoid Interactions Detected - Donald L. J. Quicke; Daniel H. Janzen; Winnie Hallwachs; Mike J. Sharkey; Paul D. N. Hebert; Buntika A. Butcher (Diversity)
Foliage-feeding wild caterpillars have been collected and reared year-round by 1–30 rural resident parataxonomists in the Area de Conservación Guanacaste (ACG) in northwestern Costa Rica since 1978. The aim of the work was to describe the diversity and interactions of Lepidoptera and their associations with larval food plants and parasitoids in a diverse tropical community. A total of 457,816 caterpillars developed into a moth or butterfly, and these were identified to the family and species/morphospecies, with 151,316 having been successfully barcoded and assigned a Barcode Index Number (BIN) and/or “scientific name”. The host food plant was usually identified to the species or morphospecies. In addition to adult moths and butterflies, rearings also yielded many hundreds of species of parasitic wasps and tachinid flies, many of which were also DNA-barcoded and assigned a name and/or BIN. Increasingly over recent years, these have been identified or described by expert taxonomists. Here, we provide a summary of the number of species of ichneumonoid (Ichneumonidae and Braconidae) parasitoids of the caterpillars, their hosts, the host food plants involved, the bi- and tritrophic interactions, and their relationships to the caterpillar sampling effort. The dataset includes 16,133 and 9453 independent rearings of Braconidae and Ichneumonidae, respectively, collectively representing 31 subfamilies, all with parasitoid barcodes and host and host food plant species-level identifications. Host caterpillars collectively represented 2456 species, which, in turn, were collectively eating 1352 species of food plants. Species accumulation curves over time for parasitoids, hosts, and plants show various asymptotic trends. However, no asymptotic trends were detected for numbers of unique parasitoid–host and host–plant bitrophic interactions, nor for tritrophic interactions, after 1983, because climate change then began to conspicuously reduce caterpillar densities. Parasitoid host ranges, the proportions of specialists at the host species and host genus levels, host family utilisation, and host guild sizes show some differences among taxa and are discussed in turn. Ichneumonidae are shown to preferentially parasitise caterpillars of larger-bodied hosts compared to Braconidae. Several of the host plant species from which caterpillars were collected have been introduced from outside of the Americas and their utilisation by endemic parasitoids is described. The obligately hyperparasitoid ichneumonid subfamily Mesochorinae is dealt with separately and its strong association with microgastrine braconid primary parasitoids is illustrated. We discuss the implications for studies of tropical insect community food web ecology and make suggestions for future work. The aim was to make available the data from this remarkable study and to provide an overview of what we think are some of the more interesting relationships that emerge—other scientists/readers are expected to have different questions that they will go on to explore the data to answer.